Tensions in the Taiwan Strait. Issue 3 (16th March 2019) - Unknown
Abstract : Despite China's recent menacing rhetorical and military gestures, armed conflict in the Taiwan Strait remains unlikely in the near-term. Chinese military intimidation has failed to achieve its desired effects on the Taiwanese population, whose identity is increasingly distinct from that of mainland Chinese. It is possible, however, that a change of government in Taipei next year will lead to closer cross-strait relations.